CEBPB promotes ulcerative colitis-associated colorectal cancer by stimulating tumor growth and activating the NF-κB/STAT3 signaling pathway - Gao Shan; Wang Wei; Tong Xu-Dong; Wang Dao-Rong; Tian Ai-Xia; Yang Wei; Chen Jin-Min (Open Life Sciences)
Ulcerative colitis-associated colorectal cancer (UCCRC) represents a significant complication of ulcerative colitis. CEBPB has been shown to promote the invasion of colon cancer cells. In this study, we aimed to investigate the role of CEBPB in the progression of cancers associated with colitis. The wild-type (WT) mice, transfected with a vector expressing CEBPB and siRNA targeting CEBPB, along with their littermate controls, were subjected to a challenge using azoxymethane and dextran sodium sulfate to establish a model of UCCRC. Colon tissues and blood samples were collected for analysis through hematoxylin and eosin staining and enzyme linked immunosorbent assay. Immunohistochemical staining was employed to assess protein expression. In the UCCRC model, mice transfected with vectors expressing CEBPB exhibited a reduction in weight loss and colorectal stenosis, as well as disordered colonic gland structure. Additionally, these mice demonstrated an increased number and size of tumors compared to WT controls. Furthermore, transfection with CEBPB resulted in a decrease in both the quantity and dimensions of tumors. NF-κB was found to enhance the phosphorylation level of STAT3 based on Western blot assay. The activation of NF-κB and STAT3 subsequently promoted the proliferation, invasion, and migration of colon cancer cells by clone formation assays, transwell assays, and scratch-wound assays. Moreover, rescue experiments indicated that CEBPB induced UCCRC through the NF-κB/STAT3 signaling pathway. CEBPB mediated colonic injury in UCCRC mice by activating the NF-κB/STAT3 pathway. This finding reveals a previously unrecognized link between CEBPB and colitis-related tumorigenesis and provides new insight into UCCRC pathogenesis.